THE ROLE OF MANAGER AS THE KEY FACTOR OF SUCCESS AT SMALL BUSINESS COMPANIES: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This thesis is aimed to analyse the phenomenon of manager at small business enterprise. It describes essential characteristics of the small business company’s manager as well as its main duties and roles within the company.